Penerapan akuntansi pertanggungjawaban sebagai alat evaluasi kinerja manajer pusat biaya pada PT. Royal Coconut Gorontalo - Timothy, Melvin Gabrielton; Gerungai, Natalia Y. Telly; Pinatik, Sherly (Yayasan Widyantara Nawasena Raharja, 2025)
Responsibility accounting is a system developed in alignment with the characteristics and activities of a company to ensure that each organizational unit can be held accountable for its performance. This study aims to analyze the implementation of responsibility accounting as a tool for evaluating the performance of cost center managers at PT Royal Coconut Gorontalo. A qualitative descriptive research method was employed. Data were collected through interviews and documentation. The findings indicate that the implementation of responsibility accounting at PT Royal Coconut Gorontalo remains suboptimal. Responsibility reports still aggregate various types of costs into a single account without clear classification. Moreover, the budgeting process is not participatory, leading to discrepancies between the predetermined budget and actual operational conditions in the field.